Identification and characterization of five polymorphic microsatellite loci in the freshwater copepod Hemidiaptomus gurneyi (Copepoda: Calanoida: Diaptomidae). Issue 1 (2nd January 2016) - Marrone, F.; Havenstein, K.; Tiedemann, R.; Ketmaier, V.
Abstract: Hemidiaptomus diaptomid copepods are known to be excellent biological indicators for the highly biodiverse crustacean communities inhabiting Mediterranean temporary ponds (MTPs), an endangered inland water habitat whose conservation is considered a priority according to the "Habitat Directive" of the European Union. This study reports on the characterization of five polymorphic microsatellite loci in Hemidiaptomus gurneyi, to be used as markers for fine-scale studies on the population genetic structure and metapopulation dynamics of a typical and obligate MTP dweller. The five selected loci proved to be polymorphic in the species, with three to five polymorphic loci per studied population. Overall, mean heterozygosity scored for all loci and populations was lower than that reported for the few other diaptomid species for which microsatellite loci have been to date described; this is possibly due to the intrinsically fragmented and isolated peculiar habitat inhabited by the species. Furthermore, the presence of indels within the flanking regions of selected loci was scored. This study, albeit confirming the technical difficulties in finding proper microsatellite markers in copepods, provides for the first time a set of useful polymorphic microsatellite loci for a Hemidiaptomus species, thus allowing the realization of fine-scale phylogeographic and population genetics studies of this flagship crustacean taxon for MTPs.